Association of socioeconomic position and childhood obesity in Finland: a registry-based study - Majid Ezzati; Hanna Tolonen; Tiina Laatikainen; Franco Sassi; Laura Paalanen; Esko Levälahti; Päivi Mäki (BMJ Open)
Objective To identify what dimensions of socioeconomic position (SEP) are most closely associated with childhood obesity in Finland, leveraging population-wide data among the whole child population aged 2–17 years in Finland.Design Registry-based study.Setting Data from several administrative registries linked on individual level covering the whole of Finland were used. Data on height and weight measurements in 2018 were obtained from the Register of Primary Health Care visits and data on sociodemographic and socioeconomic indicators (2014–2018) from Statistics Finland.Participants Children aged 2–17 years with valid height and weight measurements performed at the child health clinic or school healthcare in 2018 (final n=194 423).Main outcome measures Obesity was defined according to WHO Growth Reference curves. Sociodemographic and socioeconomic indicators were linked on individual level for adults (both parents) who lived in the same household (42 predictors). Boosted regression model was used to analyse the contribution of SEP to obesity.Results From socioeconomic indicators, annual household income (12.6%) and mother and father’s educational level (12.6% and 8.1%, respectively) had the highest relative influence on obesity risk. The relative influence of a child’s sex was 7.7%.Conclusions The parents’ SEP was inversely associated with obesity among the offspring. A remarkable number of objective SEP indicators were analysed with parents’ education and household income finally being the indicators most strongly associated with obesity among children. In future research, more attention should be paid to reliable and objective ways of measuring educational status and income rather than on developing new SEP indicators. Administrative registries with information on both healthcare and socioeconomic indicators can in future provide better opportunities to assess the influence of SEP on various health risks.